2019
DOI: 10.1089/heq.2019.0009
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities Among Mid-to-Older Deaf LGBTQ Adults Compared with Mid-to-Older Deaf Non-LGBTQ Adults in the United States

Abstract: To compare chronic health and mental health conditions between mid-to-older deaf lesbian, gay, bisexual, transgender, and queer (LGBTQ) and mid-to-older non-LGBTQ adults who are 45 years or older. Methods: Medical conditions and mental health disorders data were gathered from 981 mid-to-older deaf adults (178 LGBTQ and 803 non-LGBTQ) who took the Health Information National Trends Survey in American Sign Language between 2015 and 2019. Modified Poisson regression with robust standard errors was used to calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Kushalnagar et al [ 32 ] found that the Deaf LGBTQ population in the US, in comparison with the Deaf non-LGBTQ population, are more likely to have a personal cancer history (24.1% vs 15.2%), more likely to have a lung condition (23.4% vs 15%), and significantly more likely to experience depression/anxiety (33.3% vs 17.9%). Deaf LGBTQ status was also significantly associated with increased risk for arthritis (RR = 1.26) and for chronic comorbidity (2 or more medical conditions) (RR = 1.25) [ 32 ] in comparison with the Deaf non-LGBTQ population. A small-scale study (n = 36) reported that the LGBTQ status were not significantly related to the depression score [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kushalnagar et al [ 32 ] found that the Deaf LGBTQ population in the US, in comparison with the Deaf non-LGBTQ population, are more likely to have a personal cancer history (24.1% vs 15.2%), more likely to have a lung condition (23.4% vs 15%), and significantly more likely to experience depression/anxiety (33.3% vs 17.9%). Deaf LGBTQ status was also significantly associated with increased risk for arthritis (RR = 1.26) and for chronic comorbidity (2 or more medical conditions) (RR = 1.25) [ 32 ] in comparison with the Deaf non-LGBTQ population. A small-scale study (n = 36) reported that the LGBTQ status were not significantly related to the depression score [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another area that warrants attention in future research is the intersectionality of multiple identities among Black DHH people. The intersection of marginalized identities, including sexual orientation and gender identity, has been found to contribute to poorer health outcomes among DHH people who hold multiple marginalized identities [42,43] . Further research into the prevalence of health outcomes between Black DHH and hearing individuals who hold multiple marginalized identities may inform the impact of intersectionality on the health outcomes of DHH people, of which there is a very limited body of literature.…”
Section: Discussionmentioning
confidence: 99%
“…LGBTQ+ status: Kushalnagar et al [32] found that the Deaf LGBTQ population in the US, in comparison with the Deaf non-LGBTQ population, are more likely to have a personal cancer history (24.1% vs 15.2%), more likely to have a lung condition (23.4% vs 15%), and significantly more likely to experience depression/anxiety (33.3% vs 17.9%). Deaf LGBTQ status was also significantly associated with increased risk for arthritis (RR=1.26) and for chronic comorbidity (2 or more medical conditions) (RR=1.25) [32] in comparison with the Deaf non-LGBTQ population. A small-scale study (n=36) reported that the LGBTQ status were not significantly related to the depression score [33].…”
Section: Factors Identified As Influencing Health Outcomes Within The...mentioning
confidence: 99%